Hydrostatic massage improves the treatment of congenital naso-lacrimal duct obstruction (CNLDO) within one year of age (Journal of National Institute of Ophthalmology, 2025)
Objective: To find out the effect of hydrostatic massage as a part of conservative management of Congenital naso-lacrimal duct obstruction (CNLDO). Materials and Methods: This prospective and comparative study, was conducted on patients suffering from CNLDO and reported in outpatient department of pediatric ophthalmology in National Institute of Ophthalmology (NIO) Dhaka between January 2023 to September 2023. A protocol was submitted and after getting the approval from the ethical committee a questionnaire and a proforma was prepared for data collection, record and follow up of patients. Informed written consent was obtained from the parents. CNLDO diagnosis was made on clinical examination and sac regurgitation test. All collected data were checked and verified thoroughly to reduce the inconsistency. Quality of data was always ensured. Analysis of data was done by "Statistical Package for Social Science” (SPSS, version 24.0) in the computer. Total 200 patients were included in the study comprising 94(47%) male and 106(53%) were female within one year of age. They were divided into two groups. Group-A contained 120 patients, hydrostatic massage and topical eye drop were advised to each patient of with the regimen of 10 strokes of hydrostatic massage four times a day after demonstration the proper technique to the parents. Group-B contained 80 patients those were given only topical Eye drop but no hydrostatic massage. follow up was done after 1 to 4 months. Results: Hydrostatic massage for CNLDO in Group-A (Total120) was successful in 101 (84.16%) patients and failed in 19 (15.84%)) patients and Group B (Total 80), Not improved 66 (82.50%) patients, improved by only topical antibiotic drop 14 (17.50%) patients. Conclusion: CNLDO usually presents complaints of watering or watering with discharge. The outcome of conservative management comprises with hydrostatic massage at lacrimal sac are promising. The success rate declines with increase of age.J.Natl.Inst.Ophthalmol. 2023; 6(2): 54-57